Sleep Quality and Stress Levels Among Second-Year Nursing Students - Emil Benazir Anjani; Siti Khadijah; Dwi Ariani Sulistyowati (Interest : Jurnal Ilmu Kesehatan, 2023)
Background: Nursing students experience stress in various forms and levels, which can negatively affect their well-being if not managed properly. The accumulation of stress can lead to significant consequences if unresolved. This study analyzes the relationship between stress levels and sleep quality among second-year nursing students. Methods: This cross-sectional study used simple random sampling to select 59 nursing students. Stress levels were assessed using the Depression Anxiety and Stress Scale (DASS), while sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Data ware analyzed using the Kendall tau_b correlation test. Results: Stress level is associated with sleep quality in second year nursing students (p value 0.005). The strength of the relationship in the category is quite strong (r = 0.344). The lighter the stress level, the better the sleep quality of second-year nursing students. Conclusion: Stress levels are significantly related to sleep quality in second-year nursing students. Preventive measures and stress management strategies, such as counseling, are recommended to improve sleep quality.